Efficacy of fluticasone propionate ointment 0.005% in childhood lichen planus - Abhinav Kumar; Vibhu Mendiratta; Sarita Sanke; Ram Chander (Wolters Kluwer Medknow Publications, 2020)
Background: Treatment of childhood lichen planus (LP) is challenging owing to high rate of relapses. Moreover, majority of treatment options for LP have been extrapolated from studies done in adults. Topical corticosteroid remains the first line of treatment in localized classic form of LP, but till date, no consensus exists regarding standardized therapy in children. Hence, we conducted this study to evaluate the efficacy of mid-potent topical steroid fluticasone propionate 0.005% in childhood LP. Aims and Objectives: The aim of this study was to evaluate the therapeutic efficacy of fluticasone propionate ointment 0.005% in childhood LP. Materials and Methods: Thirty-one patients (6 months to 18 years of age) with clinical and histopathologically confirmed diagnosis of LP were subjected to routine baseline severity assessment, patient/parent assessment, pretreatment photographic record of the fixed anatomical site under treatment, and then received topical mid-potent steroid therapy (fluticasone propionate ointment 0.005%) twice daily and cetirizine dihydrochloride in predefined doses for 8 weeks. Follow-up was done at the end of 2 weeks, 4 weeks, 6 weeks, and 8 weeks. After 8 weeks, a proportion of patients achieving clinical improvement and side effects were assessed. Observation and Results: The difference between pre- and posttreatment induration was not statistically significant (P = 0.336). The mean number of lesions before the start of treatment was 50.29, which reduced to 14.77 (P = 0.000) after treatment, and the mean of patients' itching score before treatment was 6.74 ± 1.6, which reduced to 2.61 ± 2.3 (P = 0.000) following treatment, which was statistically significant. Clinical improvement was seen in 67.7%, whereas 32.3% showed no improvement over a period of 8 weeks. Conclusion: Mid-potency steroid fluticasone propionate ointment twice daily is an effective therapeutic agent for localized childhood LP, with minimal side effects.